Programming for computations – MATLAB/Octave : a gentle introduction to numerical simulations with MATLAB/Octave /: a gentle introduction to numerical simulations with MATLAB/Octave. (2016) - Linge, Svein; Langtangen, Hans Petter, 1962-
No abstract available